Genetic Diversity and Phylogenetic Relationship of Kryptoterus limpok and Kryptopterus apogon from Kampar and Indragiri River Based on Cytochrome b Gene - Roza Elvyra; Dedy Duryadi Solihin; Ridwan Affandi; Zairin Junior; Yusnarti Yus (Jurnal Ilmu-Ilmu Perairan dan Perikanan Indonesia, 2009)
The utility of cytochrome b gene as a molecular marker to obtain genetic diversity and phylogenetic relationship among Kryptopterus spp. consist of Kryptopterus limpok and Kryptopterus apogon from Riau Province has been studied. The universal primers of (F) L14841 and (R) H15149 were used to amplify the cytochrome b gene. The results of multiple allignment were 159 nt (coding 53 amino acids). Kryptopterus limpok from Kampar and Indragiri River form a phylogeny cluster at 80% bootstrap value. Kryptopterus apogon from Kampar and Indragiri River form a phylogeny cluster at 99% bootstrap value.Keywords : cytochrome b, Kryptopterus limpok, Kryptoperus apogon.